Pertanggungjawaban Kuasa Pengguna Anggaran (KPA) dalam Proses E-Purchasing Barang dan Jasa Pemerintah - Redha Ardiyanti (Jurnal Ragam Pengabdian, 2026)
The transformation of government procurement of goods and services towards an electronic system (E-Purchasing) via E-Catalogue is intended to increase transparency, accountability, and efficiency in state spending. However, the common assumption that this system is entirely free from legal risk is misguided and dangerous, given that potential fraud such as price markups, fictitious specifications, and malicious collusion remains even within digital platforms. This study aims to analyze in depth the limits of the legal liability of the Budget User Proxy (KPA) in the E-Purchasing mechanism. Using a normative juridical research method with statutory and conceptual approaches, this study finds that KPA cannot absolve themselves of absolute responsibility to the Commitment Making Official (PPK) solely on technical grounds. The KPA bears administrative liability in cases of supervisory negligence and can be drawn into the realm of criminal corruption if there is proven intent (dolus) or omission regarding irregularities that cause state financial losses. Therefore, the inherent supervisory function of the KPA becomes a vital instrument and the final stronghold in preventing electronic procurement corruption.